Infuence of additional players on collective tactical behavior in small-sided soccer games - Praça, Gibson (2016)
e aim of this study was to compare the collective tactical behavior between numerically balanced and unbalanced small-sided soccer games. Eighteen male soccer players (mean age 16.4 years) participated in the study. Polar coordinate analysis was performed using positional data obtained with a 15-Hz GPS device. Collective variables including length, width, centroid distance (average point between teammates), and length per width ratio (LPWratio) were collected. Data were analyzed using Friedman’s test. e results showed greater length and width values in 4vs.3 games, while a higher LPWratio was observed in 3vs.3+2 games compared to the other con gurations. In games with an additional player (4vs.3), ball circulation and the increase in e ective game space were alternatives to overcome the more concentrated defensive systems near the goal. On the other hand, 3vs.3+2 games allowed more actions in the length axis and a fast reach of the opponent’s goal.